PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 1 TALAMAU KABUPATEN PASAMAN BARAT - Tisnim, Tisnim; Anggraini, Villia; Rahima, Rahima (Pendidikan Matematika, 2014)
ABSTRACTThis research was background by student understanding of mathematical concept is still low and the students do not have responsiblity in do Â the group task. He aim of this research model is to know the understanding of mathematical concepts by applying model study with cooperative type Numbered Heads Together Â Accompanied Quiz better than student in understanding mathematical concepts with conventional learning. This research is to design Â experimental with random subject. Instrument used in this research is the quiz and final test . Form of tes the used is form of essay with r11 = 0.816. Based on the analysis of data the are development of understanding mathematical concepts. From the test result obtained tcount = 2.031 greater than ttable = 1,682 . So that can be concluded studentsâÂ  understanding of mathematical concepts apply cooperative learning model Numbered Heads Together accompanied by quiz better than understanding of mathematical concepts students applying conventional learning in Â the class VIII SMPN 1 Talamau.